Experimental and numerical study on cavitation flow characteristics of refrigerants with different thermophysical properties in confined micro-clearance - Shaohang Yan; Tianwei Lai; Zhen Wang; Qi Zhao; Yu Hou (Case Studies in Thermal Engineering)
In high-speed hydraulic machinery, its efficiency and reliability are affected by the cavitation in the bearing. Due to the confined effect of the bearing clearance, cavitation bubbles grow in a two-dimensional way. To uncover the cavitation process with confined and high speed shearing effect, the high-speed cavitation flowing of different refrigerants is researched experimentally based on the high-speed shearing test rig with micro-clearance. The influence of thermophysical properties on growth of cavitation bubble is evaluated and analyzed. The confined effect of micro-clearance and high-speed shearing effect has a significant influence on the cavitation bubbles evolution. The high-speed camera is used to record the morphology of cavitation bubbles for various refrigerants with different thermalphysical properties. Furthermore, the thermal-sensitive cavitation model is used to analyze the bubble-foam alternation from cavitation flow inside micro-clearance. For different refrigerants, the growth process of cavitation bubble area is exponential. Inside the micro-clearance, the cavitation inducing pressure drops of different refrigerants are analogous due to the similar thermodynamic properties. According to pressure drop during cavitation, different refrigerants are classified by introducing dimensionless numbers, σ·Re (Jie et al., 2009) [2] and σ·We. The pressure and temperature drop increase with the dimensionless numbers. The refrigerants with similar thermodynamic properties have a similar relationship between dimensionless number and supercooling degree.